2014
DOI: 10.1007/s00204-014-1292-9
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent clearance of gold nanoparticles from lungs of Sprague–Dawley rats after short-term inhalation exposure

Abstract: Gold nanoparticles are known to be distributed to many tissues following their oral, inhalation, or intravenous exposure. Information on the biodistribution and clearance of gold nanoparticles from these tissues is, therefore, important to understand their behavior in vivo. To study the effect of size on the biodistribution of gold nanoparticles, Sprague-Dawley rats were exposed by inhalation to small gold nanoparticles (13 nm in diameter on average) at an exposure concentration of 12.8 ± 2.42 µg/m(3), and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 15 publications
1
49
0
1
Order By: Relevance
“…This reinforces the suggestion that translocation and accumulation of NMs may be size-dependent with the smaller Au NMs more readily distributed to extra-pulmonary tissues than the larger NMs. The data from the study suggests possible clearance mechanisms for the materials over time -with the clearance via the reticuloendothelial system as highlighted by increasing levels of NMs in the spleen over time (Han et al 2014).…”
Section: Inhalation Exposurementioning
confidence: 85%
See 1 more Smart Citation
“…This reinforces the suggestion that translocation and accumulation of NMs may be size-dependent with the smaller Au NMs more readily distributed to extra-pulmonary tissues than the larger NMs. The data from the study suggests possible clearance mechanisms for the materials over time -with the clearance via the reticuloendothelial system as highlighted by increasing levels of NMs in the spleen over time (Han et al 2014).…”
Section: Inhalation Exposurementioning
confidence: 85%
“…Several studies have noted that the pattern of distribution tends to be size and charge dependent (Hirn et al 2011) with markedly greater bio-distribution and accumulation of NMs in comparison to larger materials of the same chemical composition (Han et al 2014, Liu et al 2012b. Additionally, it has been suggested that smaller NMs can bind lung-lining layer proteins and use them as transporting vehicles across membranes, whereas micro-particles would be excluded from this transport mechanism (Lynch and Dawson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a size-dependent bioaccumulation was demonstrated for AuNPs (5, 15, and 40 nm) in the Tellinid clam Scrobicularia plana (Pan et al 2012), in which a greater accumulation was confirmed for larger NPs. Similarly, longer half-lives (T 1/2 s) and mean residence times that may lead to greater bioaccumulation were observed for larger AuNPs than smaller AuNPs (Han et al 2015). Although a greater accumulation was also observed for larger bovine serum albuminstabilized 7.8-, 15-, and 46-nm AuNPs in filter-feeding bivalves (Corbicula fluminea; Hull et al 2011), a greater accumulation in the tilapia species Oreochromis niloticus was observed for smaller ZnONPs (10-30 nm) than for larger NPs (100 nm; Kaya et al 2015).…”
Section: Factors That Affect Bioaccumulation Of Nmsmentioning
confidence: 85%
“…Clearance of particles deposited in the lungs is known to depend mainly on the dose, size, shape and dissolution rate of primary particles and their aggregates and agglomerates (Greim and Ziegler-Skylakakis 2007;Keller et al 2014). Previous studies investigating the influence of particle size on the clearance have either found no influence of particle size on clearance (Semmler et al 2004;Buckley et al 2017) or a slower clearance of smaller particles (Geraets et al 2012;Keller et al 2014;Han et al 2015).…”
Section: Differences Due To Different Nanoformsmentioning
confidence: 99%